Successful therapy using high-dose furmonertinib for non-small cell lung cancer with leptomeningeal metastasis: a case report and literature review - Chen, Ting; Chen, Jie; Liu, De-sheng; Shu, Yan-ling; Fu, Mao-yue; Gou, Hai-jun; Lei, Kai-jian; Jia, Yu-ming (Frontiers in Oncology, 2023)
Background: Lung cancer is the second most common malignant tumor and carries the highest mortality worldwide. Among its subtype, lung adenocarcinoma is the most prevalent. Leptomeningeal metastasis (LM) is rare and characterized by a dismal prognosis, with an overall survival typically spanning 4 to 6 weeks without treatment.However, in specific cases, survival can be extended to 4 to 6 months with appropriate therapy. The recent approval of third-generation tyrosine kinase inhibitors (TKIs), such as osimertinib, aumolertinib, and furmonertinib, has brought promising treatment options for individuals with non-small cell lung cancer (NSCLC) who develop LM after developing resistance to first-and second-generation TKIs. These third-generation TKIs exhibit enhanced ability to penetrate the blood-brain barrier (BBB), opening up new avenues for managing this challenging condition.